PERAN PEMUDA RELAWAN DEMOKRASI DALAM MENINGKATKAN PARTISIPASI POLITIK MASYARAKAT PADA PEMILIHAN UMUM LEGISLATIF TAHUN 2014 DAN IMPLIKASINYA TERHADAP KETAHANAN POLITIK WILAYAH (STUDI PADA RELAWAN DEMOKRASI BANYUMAS, JAWA TENGAH) - Fuad, Zamzam Muhammad (Jurnal Ketahanan Nasional, 2015)
This research was going to described the role of Banyumas Democracy Volunteer ( Relawan Demokrasi Banyumas) in increasing political public partitipation in Banyumasâs legislative election 2014 and its implication to Banyumasâs political resilience. This research used qualitative research design as a research method. Data were collected by in depth review, observation and documentation. This research used purpossive sampling technique with stakeholder sampling variant to pick informants. The research showed that Banyumas Democracy Volunteer had a positive role in developing political resilience in Banyumas. Their role was gave political education and election education to voters in Banyumas. In the other words, Banyumas Democracy Volunteer had a vital role in developing ideal political resilience in Banyumas.Keywords: Banyumas Democracy Volunteer, Democracy, Election, Political Resilience of Region.